The Impact of Tactical Skills in Promoting Harmonious Learning Environment among Undergraduate Students - Moses Adeleke Adeoye; Rasheedat Modupe Oladimeji; Joshua Durotoye Jolaoye; Kamoru Abidoye Tiamiyu; Abdulrazak Mohammed (Universitas Pendidikan Ganesha, 2023)
Tactical skills refer to effective communication and conflict resolution strategies that can be used to address challenging situations calmly and respectfully. The theoretical framework draws on social learning theory and situational leadership theory. This study aims to analyze the impact of tactical skills on promoting a harmonious learning environment among undergraduate students. The method used in this research is Systematic Literature Review (SLR). The researchers collected journal articles from Google Scholar, Research Gate, SINTA, Scopus and Web of Science. The result of this study highlights the significance of tactical skills in fostering positive relationships among students, promoting effective communication and addressing conflicts in the learning environment. This study discusses examples of tactical skills such as active listening, positive framing, and collaborative problem-solving. It also addresses common challenges to promoting a harmonious learning environment, including student conflicts, disruptive behavior, cultural differences, and lack of resources and provides strategies for overcoming these challenges. The paper also examines relevant empirical studies that support the role of tactical skills in promoting a harmonious learning environment. Finally, the paper concludes that educators and administrators should prioritize the development of tactical skills in their teaching and learning practices to create a more inclusive and collaborative learning environment.